The Optimal Graduated Minimum Wage and Social Welfare - Eliav Danziger; Leif Danziger (Global Labor Organization (GLO), 2018)
This paper analyzes the effects of introducing a graduated minimum wage in a model with optimal income taxation in which a government seeks to maximize social welfare. It shows that the optimal graduated minimum wage increases social welfare by increasing the low productivity workers' consumption and bringing it closer to the first-best. The paper also describes how the graduated minimum wage in a social welfare optimum depends on important economy characteristics such as the government's revenue needs, the social-welfare weight of low-productivity workers, and the numbers and productivities of the different types of workers.
Keywords: D60; H21; J30; 330; Graduated minimum wage; optimal income taxation; social welfare